Social Protection Programmes - Semprebon, Michela (Taylor & Francis, 2023)
This book deals with social protection programmes targeted to people trafficked for the scope of sexual exploitation. It provides empirical evidence on the N.A.Ve programme, in the north-eastern Italian Veneto Region, and its evolution. It elaborates on the programme by narrating the subjective experiences of practitioners and of a specific group of beneficiaries: young Nigerian women - some in transition towards the majority age.